Use of Quality Models and Indicators for Evaluating Test Quality in an ESP Course - RUDZINSKA, IEVA (Journal of Education Culture and Society, 2020)
Qualitative methods of assessment play a decisive role in education in general and in language learning in particular. The necessity to perform a qualitative assessment comes from both increased student competition in higher education institutions (HEIs), and hence higher demands for fair assessment, and a growing public awareness on higher education issues, and therefore the need to account for a wider circle of stakeholders, including socie-ty as a whole. The aim of the present paper is to study the regulations and laws pertaining to the issue of assessment in Latvian HEIs, as well as to carry out literature sources analysis about assessment in language testing, seeking to select criteria characterizing the quality of English for Specific Purposes (ESP) tests and to apply the model of evaluating the quality of a language test on an example of a test in sport English, developed in a Latvian higher education institution. An analysis of the regulations and laws about assessment in higher education and li-terature sources about tests in language courses has enabled the development of a test qu-ality model, consisting of seven intrinsic quality criteria: clarity, adequacy, deep approach, attractiveness, originality/similarity, orientation towards student learning result/process, test scoring objectivity/subjectivity. Quality criteria comprise eleven indicators. The relia-bility of the given model is evaluated by means of the whole model, its criteria and indica-tor Cronbach’s alphas and point-biserial (item-total) correlations or discrimination indexes DI. The test was taken by 63 participants, all of them 2nd year full time students attending a Latvian higher education institution.A statistical data analysis was performed with SPSS 17.0. The results show that, altho-ugh test adequacy and clarity is sufficiently high, attractiveness and deep approach should be improved. Also the reliability of one version of the test is higher than that of the other one. One of the ways to improve test quality could be to involve other HEIs in the process of designing tests, because in a small institution it is difficult to collect authentic material for test design and create reliable language tests in a narrow field (in our case: sport English).